Job Satisfaction and Self-Realization of Bookmakers - TROFIMOV, Andrii; MILIUTINA, Kateryna; BULATEVYCH, Nataliya; MAKSYMOV, Mykola; NEVIDOMA, Yana; BILOUS, Oleksandr (Journal of Advanced Research in Law and Economics, 2017)
This study focuses on the analysis of the problem of job satisfaction in such field of activity as employees of bookmaker offices. In this area of business, the success of activities is closely related to work experience, employees require special training, therefore prevention of staff turnover is one of the important tasks of management. In the field of psychological research, the problem arises of finding external and internal factors of satisfaction with work. The purpose of this article is to identify factors of job satisfaction among employees of bookmakers. There were 35 men with higher education, who took part in the study. The influence of objective factors on the level of satisfaction was studied: age, education, duration of work at the enterprise. The influence of age and education was not revealed. Education of respondents were both technical and humanitarian, both secondary special and higher, which did not affect the level of satisfaction with work. Respondents differed in the length of their work at this workplace. As a methods of research were used: To study organizational commitment, we used:  questionnaire ‘Scale of organizational commitment’; subscale ‘Alienation from work’; PSYCAP, UWES, LOT Life Orientation Test and The HARDI-SURVEY technique; Generalized self-efficacy scale (R. Schwarzer, and M. Jerusalem) and Adult Dispositional Hope Scale, ADHS (C. R. Snyder); Methodology of self-actualization of personality by Lazukin. It was found that the involvement in their work is associated with affective commitment and self-efficacy, while the pursuit for self-realization, creativity negatively affects the involvement, and alienation from work does not prevent involvement.